Matematică
IuliaBoar
38

Efectuati a)(2x-1) (x+3)-2(x²+x+1) b)(x-3) {2x-3(x-1)]+x(x+5) c)(3x-7) {3(x+1)-2(x+3] -2x(x+6) d) (2x+5) [5(x+1)+2(x-2)] -4x(5x-4) e)(x+5) [ 3x-2(x+2)-2(x+2)]-x(x+4)

+3
(1) Răspunsuri
Meryiii

a) (2x-1)(x+3)-2(x²+x+1)=2x^2+5x-3-2x^2-2x-1=3x-4 b) (x-3) {2x-3(x-1)+x(x+5)}=(x-3)(2x-3x+3+x^2+5x)= =(x-3)(x^2+4x+3)=(x-3)(x+1)(x+3) c) (3x-7) {3(x+1)-2(x+3] -2x(x+6)}=(3x-7)(3x+3-2x-6-2x^2-2x)= =(3x-7)(-2x^2-x+3)=(3x-7)(x-1)(-2x-3)=-(3x-7)(x-1)(2x+3) d) (2x+5) [5(x+1)+2(x-2)] -4x(5x-4)]= (2x+5)(5x+5+2x-4-20x^2+16x)= = (2x+5)(-20x^2+23x+1) e) (x+5) [ 3x-2(x+2)-2(x+2)]-x(x+4)]= (x+5)(3x-2x-4-2x-4-x^2-4x)= = (x+5)(-x^2-5x-8)=-(x+5)(x^2+5x+8) Sper ca enunturile au fost corecte, am lucrat pe materialul clientului.

Adaugă răspuns